2004
DOI: 10.1080/13693780310001624574
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel, simple and rapid molecular identification system for clinicalCandidaspecies

Abstract: Identification of clinical yeast isolates causing candidiasis is routinely performed by commercial yeast identification systems based on biochemical, morphological and physiological tests. These systems require 3-5 days and the proportion of identifications that are incorrect is high. Our novel and rapid molecular identification system for clinical Candida species is based on the analysis of restriction patterns obtained from PCR-generated ribosomal DNA sequences using five restriction enzymes. A software pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…With our work, we added a new dimension to the fundamental work of Deak et al. (2004), who have applied this method in a rapid molecular identification system for clinical Candida species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With our work, we added a new dimension to the fundamental work of Deak et al. (2004), who have applied this method in a rapid molecular identification system for clinical Candida species.…”
Section: Resultsmentioning
confidence: 99%
“…With our work, we added a new dimension to the fundamental work of Deak et al (2004), who have applied this method in a rapid molecular identification system for clinical Candida species. We showed that natural isolates of ascomycetous or basidiomycetous yeasts can also be identified by in silico RFLP.…”
Section: Comparison Of In Silico Rflp and Conventional Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Maiwald et al 21 introduced a method for presumptive differentiation of 12 clinically relevant yeasts to the species level by amplification of the small ribosomal subunit 18S-rRNA using six enzymes. Identification of Candida species by PCR-RFLP has also been applied recently by Deak and Pinto 22,23 . While all of the mentioned studies discriminated Candida species using several restriction enzymes, we identified six species, which accounts for up to 95% of Candida infections, using only one enzyme.…”
Section: Discussionmentioning
confidence: 99%